Malaysian Fermented Shrimp Paste (belacan): A Source of Potential Probiotic Lactic Acid Bacteria - Ilyanie, H. Y.; Nur Huda Faujan; Ida Muryany, M. Y (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus